5(x-3)=-2(6-x)+2x

Simple and best practice solution for 5(x-3)=-2(6-x)+2x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(x-3)=-2(6-x)+2x equation:



5(x-3)=-2(6-x)+2x
We move all terms to the left:
5(x-3)-(-2(6-x)+2x)=0
We add all the numbers together, and all the variables
5(x-3)-(-2(-1x+6)+2x)=0
We multiply parentheses
5x-(-2(-1x+6)+2x)-15=0
We calculate terms in parentheses: -(-2(-1x+6)+2x), so:
-2(-1x+6)+2x
We add all the numbers together, and all the variables
2x-2(-1x+6)
We multiply parentheses
2x+2x-12
We add all the numbers together, and all the variables
4x-12
Back to the equation:
-(4x-12)
We get rid of parentheses
5x-4x+12-15=0
We add all the numbers together, and all the variables
x-3=0
We move all terms containing x to the left, all other terms to the right
x=3

See similar equations:

| 258=72-u | | 1000x+50=2000x+100 | | 1000x+50=2000+100 | | -x+3-5x=10x | | x+28+47=90 | | -8+3x=3x-8 | | 10.5x=1.25x+800 | | 12x-610=0 | | 50=10(d-91) | | w/2+7=w/3 | | 35=-7s+14 | | 4n-7=-59 | | 2x+35+75=180 | | 22=k/3+19 | | (2x*1)-(4x)2=(-3x)2+2x+1 | | 2(x+30)+3x=135 | | -7(6+s)=49 | | 28=4s+28 | | 2x+10=6x-12-18 | | 6(3)+4y=38 | | j/8+20=25 | | 75x+35=225x+35 | | X+3x+3x/2=77 | | 11-3n=-1n-75 | | (3+y)(4y-1)=0 | | x+1=2(5x-4) | | -8+5=7-8b-2 | | 7x2-168=-35x | | X=6+2x-10 | | 9(4)-3y=-18 | | r/7+52=60 | | 9-x+x+3x=106 |

Equations solver categories